2011
DOI: 10.1055/s-0037-1621757
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of topical sevoflurane on venous leg ulcer with intractable pain

Abstract: SummaryWe are presenting the case of a patient with a very painful venous ulcer for whom therapy with different analgesic combinations (including acetaminophen, metamizol, tramadol, morphine, fentanyl, buprenorphine, pregabal-in, gabapentin, as well as applications of lido-caine/prilocaine eutectic cream and infusion of epidural ropivacaine) was unsatisfactory. Analgesic control was finally achieved through applications of liquid sevoflurane to the wound, which resulted in immediate, intense, and long-lasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
(8 reference statements)
1
24
0
2
Order By: Relevance
“…Our results show that topical sevoflurane have an epithelising effect, diminishing the time to healing. In previous reports, a progressive diminishing of size and deepness of the ulcer treated with sevoflurane in successive cleanings along some weeks has been reported .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our results show that topical sevoflurane have an epithelising effect, diminishing the time to healing. In previous reports, a progressive diminishing of size and deepness of the ulcer treated with sevoflurane in successive cleanings along some weeks has been reported .…”
Section: Discussionmentioning
confidence: 87%
“…Topical sevoflurane has an intense, quick and long‐lasting analgesic effect. The latency time varies between 1 and 10 minutes, and the duration ranges between 7 and 24 hours . Until now, we report the study with the highest number of patients with chronic venous ulcers treated with topical sevoflurane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical or subcutaneous sevoflurane has a reversible local and peripheral analgesic effect that has been clinically tested and is concentration-dependent, which is probably caused due to a sufficient partial pressure in the peripheral nociceptors that block the transmission of pain stimulus (6)(7)(8)(9). Topical sevoflurane has been reported in the literature as an analgesic treatment for vascular leg ulcers that are refractory to usual analgesics (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Geronimo-Pardo et al (2) reported the first case of a 76-year-old female with several risk factors of cardiovascular disease and bilateral painful venous ulcers that were treated with 5 ml of topical sevoflurane daily. An intense analgesic effect was reported in 2 minutes that lasted 12 hours.…”
mentioning
confidence: 99%